2020
DOI: 10.2174/1381612826666200331093207
|View full text |Cite
|
Sign up to set email alerts
|

Neuropharmacological Characterization of Dioclea altissima Seed Lectin (DAL) in Mice: Evidence of Anxiolytic-like Effect Mediated by Serotonergic, GABAergic Receptors and NO Pathway

Abstract: Background: Plant lectins has shown promising biological activities in the central nervous system (CNS). Objective: This study evaluated the effect of DAL, a lectin isolated from the seeds of the Dioclea altissima species, has binding affinity to D-glucose or D-mannose residues, on mouse behavior. Methods: Mice (n=6/group) were treated (i.p.) with DAL (0.25, 0.5 or 1 mg/kg) or vehicle and submitted to several tests (open field/OFT, marble-burying/MBT, hole-board/HBT, elevated plus maze/PMT, tail susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Animal head-dipping behavior remains closely correlated with their psychological response. Gamma amino-butyric acid (GABA) can modulate the central nervous system through the voltage-gated Ca 2+ channel or chlorine conductance [40][41][42][43][44][45][46][47][48][49][50]. It was revealed that the animals' head-dipping behavior is clearly relevant to their mental state, and this test is used to investigate anxiety-related activities.…”
Section: Discussionmentioning
confidence: 99%
“…Animal head-dipping behavior remains closely correlated with their psychological response. Gamma amino-butyric acid (GABA) can modulate the central nervous system through the voltage-gated Ca 2+ channel or chlorine conductance [40][41][42][43][44][45][46][47][48][49][50]. It was revealed that the animals' head-dipping behavior is clearly relevant to their mental state, and this test is used to investigate anxiety-related activities.…”
Section: Discussionmentioning
confidence: 99%
“…A large amount of flavonoids in M. oleifera leaves can interact with GABA receptors like a benzodiazepine molecule [53,64]. Additionally, evidence has suggested the possible binding of plant lectins to GABAergic receptors [65]. Together, both constituents of MoLE may be responsible for improving the inhibitory signaling of GABA receptors.…”
Section: Discussionmentioning
confidence: 99%
“…in Swiss mice. Its effect was mediated by the serotonergic and GABAergic systems as well as NO pathway [73].…”
Section: Ftl (Frutalin) α-D-galactose-binding Lectin Frommentioning
confidence: 99%